Strategic management of technological innovation - Melissa A. Schilling (New York, New York : McGraw Hill Education, 2020)
"This book approaches the subject of innovation management as a strategic process. It is organized to mirror the strategic management process used in most strategy textbooks, progressing from assessing the competitive dynamics of a situation to strategy formulation, to strategy implementation."--Publisher's description
Keywords: Innovations Gestion; Technological innovations Management; Strategic planning; New products Management